Comparison between Nasopharyngeal and Saliva Samples for the Detection of Respiratory Viruses in Children with Acute Lower Respiratory Tract Infections: A Pilot Study - Danilo Buonsenso; Piero Valentini; Francesco Mariani; Silvia Di Noi; Sofia Mazza; Ivana Palucci; Maurizio Sanguinetti; Michela Sali (MDPI AG, 2023)
Purpose: During the COVID-19 pandemic, the use of salivary swabs (SS) to detect the SARS-CoV-2 virus has been implemented and widely studied in adults and children. However, the role of SS in detecting other common respiratory viruses in children is poorly investigated. Methods: Children younger than 18 years of age admitted with respiratory signs and symptoms underwent both nasopharyngeal and SS procedures. Sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of SS were calculated, considering the nasopharyngeal swab result as the gold standard. Results: A total of 83 patients (44 females, 53%) underwent both nasopharyngeal and SS procedures. Overall, the sensitivity of SS was 49.4%. Sensitivity according to different respiratory viruses ranged from 0% to 71.43%, while the specificity ranged from 96% to 100%. Negative predictive value ranged from 68.06% to 98.8%, while positive predictive value ranged from 0 to 100%. SS sensitivity in patients younger than 12 months of age was 39.47%, while in patients older than or equal to 12 months of age it was 57.78%. Patients with negative SS had a significantly lower median age (8.5 months (15.25) vs. 23 months (34), p = 0.001) and a significantly lower quantity of median saliva collected for salivary analysis (0 μL (213) vs. 300 μL (100), p < 0.001). Conclusions: SS has a relatively low sensitivity in detecting common respiratory viruses in children with LRTI, with a lower probability in younger children (and in particular those younger than 6 months of age) or those from whom we have collected lesser amounts of saliva. New strategies to improve saliva collection are needed for testing on a larger study population.